2009
DOI: 10.1152/ajpregu.90627.2008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects and mechanisms of intestinal electrical stimulation on gastric tone, antral contractions, pyloric tone, and gastric emptying in dogs

Abstract: The aim of this study was to investigate the effects and mechanisms of intestinal electrical stimulation (IES) on gastric tone, antral and pyloric contractions, and gastric emptying in dogs. Female hound dogs were equipped with a duodenal or gastric cannula, and one pair of serosal electrodes was implanted in the small intestine. The study consisted of five different experiments. Liquid gastric emptying was assessed by collection of chyme from the duodenal cannula in a number of sessions with and without IES a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…Acceleration in gastric emptying of solid food, which precipitates hunger and frequent eating, was reported in obese subjects [44][45][46] and DIO rats [16,47]. IES with long pulses of 100 to 300 ms was noted to reduce gastric tone and delay gastric emptying in canine [48,49] and rats [13]. In the present study, IES of 3 ms was able to delay solid gastric emptying in addition to its effect on intestinal transit.…”
Section: Discussionsupporting
confidence: 61%
“…Acceleration in gastric emptying of solid food, which precipitates hunger and frequent eating, was reported in obese subjects [44][45][46] and DIO rats [16,47]. IES with long pulses of 100 to 300 ms was noted to reduce gastric tone and delay gastric emptying in canine [48,49] and rats [13]. In the present study, IES of 3 ms was able to delay solid gastric emptying in addition to its effect on intestinal transit.…”
Section: Discussionsupporting
confidence: 61%
“…In one previous canine study, IES with long pulses was shown to inhibit gastric tone and the inhibitory effect was mediated by both vagal and nitrergic pathways [18]. In another canine study, IES with long pulses was reported to inhibit antral contractions and delay gastric emptying [20]. Similarly, intestinal contractions in dogs were also attenuated with IES of long pulses and the inhibitory effect was mediated via the sympathetic pathway [6].…”
Section: Discussionmentioning
confidence: 99%
“…Each dog was studied for four sessions in a randomized order: control, mirtazapine (45 mg), RD, and RD ϩ mirtazapine (45 mg). Gastric tone and accommodation were assessed using an established method of Barostat (Distender Series IIR, G & J Electronics, Willowdale, Ontario, Canada) (36,41,45). Gastric volume was recorded for 30 min in the fasting state and 30 min after a liquid meal (237 ml, 240 kcal, Boost) in the sessions without RD, and for 60 min in the fasting state and 60 min after the liquid meal in the sessions with RD, in which RD was performed during the second 30-min fasting period and first 30-min postprandial period.…”
Section: Experimental Protocols Experiments 1: Assessment Of Complete mentioning
confidence: 99%